2019
DOI: 10.1101/634915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CLN3 regulates endosomal function by modulating Rab7A activity

Abstract: Mutations in CLN3 are a cause of juvenile NCL (JNCL), also known as Batten Disease.Clinical manifestations includes cognitive regression, progressive loss of vision and motor function, epileptic seizures, and a significantly reduced lifespan. CLN3 localizes to endosomes and lysosomes, and has been implicated in intracellular trafficking and autophagy. However, the precise molecular function of CLN3 remains to be elucidated. We show that CLN3 interacts with Rab7A, a small GTPase that regulates several functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Various neuronal deficits have been shown in in vitro models of the disease, including increased susceptibility to glutamatergic excitotoxicity (Kovacs et al, 2006;Finn et al, 2011), alterations in synaptic plasticity (Grünewald et al, 2017;Studniarczyk et al, 2018), impaired synaptogenesis (Gomez-Giro et al, 2019), and network dysfunction (Ahrens-Nicklas et al, 2019;Ahrens-Nicklas et al, 2022), but none of these have been linked directly to a molecular function for the protein. A recent study demonstrated that CLN3 regulates the retromer-dependent recycling of lysosomal sorting receptors (Yasa et al, 2020;Yasa et al, 2021), which could prove to be an important development for the field (Cotman and Lefrancois, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Various neuronal deficits have been shown in in vitro models of the disease, including increased susceptibility to glutamatergic excitotoxicity (Kovacs et al, 2006;Finn et al, 2011), alterations in synaptic plasticity (Grünewald et al, 2017;Studniarczyk et al, 2018), impaired synaptogenesis (Gomez-Giro et al, 2019), and network dysfunction (Ahrens-Nicklas et al, 2019;Ahrens-Nicklas et al, 2022), but none of these have been linked directly to a molecular function for the protein. A recent study demonstrated that CLN3 regulates the retromer-dependent recycling of lysosomal sorting receptors (Yasa et al, 2020;Yasa et al, 2021), which could prove to be an important development for the field (Cotman and Lefrancois, 2021).…”
Section: Introductionmentioning
confidence: 99%